Programming Environments and System Development Environments - Sørgaard, Pål (DAIMI Report Series, 1988)
This report discusses the nature of programming environments and system development environments under the common term development environments. Five dimensions for the characterisation of development environments are identified. These are: the system development functions supported, the kind(s) of work supported, the suitability for prototyping, the application area, and the technical properties of the environments. These dimensions are not independent. Some schools or traditions within this field are identified using these dimensions. It is argued that computer support can be provided for all system development functions. Care must be taken, however, to allow for the necessary interplay between the different system development functions. Technical properties like integration, incrementality, and tailorability may support this interplay. They may also lead to a change in the role of programming in system development. Programming will become more integrated in all parts of system development. This will make the classical division of work between analyst and programmers less obvious.